PENGARUH HUTANG JANGKA PENDEK DAN HUTANG JANGKA PANJANG TERHADAP PROFITABILITAS PADA PT. JASA MARGA (PERSERO) TBK PERIODE 2013-2023 - Andrianto , Riki; Kartono (Jurnal Nusa Manajemen, 2025)
This study aims to determine how the effect of Short-Term Debt and Long-Term Debt on Profitability through the financial statements of PT Jasa Marga (Persero) Tbk for the period 2013-2023. This type of research uses quantitative research and the analysis methods used in this research are Descriptive Statistical Analysis, Classical Assumption Test, Model Feasibility Test, Multiple Linear Regression Analysis and Hypothesis Testing. The results of the study partially show that the short-term debt variable has a tcount < ttable = (0.126 < 2.306) and a significance value (0.903 > 0.05) which means that there is no significant effect of the short- term debt variable on profitability and the long-term debt variable has a tcount < ttable = (-1.175 < 2.306) and a significance value (0.275 > 0.05) which means that there is no significant effect of the long-term debt variable on profitability. And simultaneously the short-term debt variable and the long-term debt variable also show no significant effect on profitability with the results of the f test resulting in fcount < ftabel = (0.853 < 4.26) and a significance value (0.461 > 0.05) with the coefficient of determination of this study only 17.6% while the remaining 82.4% is influenced by other variables outside this regression equation.